Comparing the Structured Multidisciplinary work Evaluation Tool (SMET) questionnaire with technical measurements of physical workload in certified nursing assistants in a medical ward setting. (October 2021) - Haraldsson, P.; Areskoug-Josefsson, K.; Rolander, B.; Strengbom, E.; Jonker, D.
Abstract: The Certified Nursing Assistant (CNA) is an important part of the workforce in hospitals and nursing homes, whose work includes heavy and repetitive work tasks including patient manual handling. The Structured Multidisciplinary work Evaluation Tool (SMET) questionnaire is an Occupational Health Service method for evaluation of the work environment. The aim of this study is to compare the SMET questionnaire with technical measurements of physical workload in CNAs in a medical ward setting. 16 CNA's participated voluntarily to 8 h of measurements during one workday. Physical workload was measured with surface electromyography and inclinometers, and the work environment was evaluated with the SMET questionnaire during the same working day. Spearman's rho was used in the statistical correlation analysis between measurements. This study shows strong, statistically significant correlations between the items in the SMET questionnaire and measured physical workload, n CNAs. Highlights: SMET is an occupational health service method for work environment management. Comparisons of items in the SMET questionnaire and measured physical workload. The SMET questionnaire is reflecting true physical workload in nursing assistants.